Oxygen Evolution Reaction on 2D Ferromagnetic Fe3GeTe2: Boosting the Reactivity by the Self‐Reduction of Surface Hydroxyl. (28th August 2019) - Zhao, Yinghe; Gu, Jinxing; Chen, Zhongfang
Abstract: Fe3 GeTe2 is a water‐ and air‐stable, metallic, and layered material. Very recently, few‐layer and single‐layer Fe3 GeTe2 have been successfully exfoliated from its bulk and revealed as 2D ferromagnets ( Nature 2018, 563, 94; Nat. Mater .2018, 17, 778). Here, the basal plane of Fe3 GeTe2 is demonstrated to be of high electrocatalytic activity towards oxygen evolution reaction (OER) without resorting to any chemical modifications, by means of systematic density functional theory computations. The Fe3 GeTe2 nanosheet preserves the metallic character of the bulk, and its 2D layered structure provides abundant exposed active sites to catalyze OER. All these unique characteristics suggest that the Fe3 GeTe2 nanosheet may be an excellent catalyst for electrochemical OER. More importantly, it is found that the self‐reduction of surface hydroxyl into water can significantly reduce the overpotential for OER, which greatly boosts the OER activity. This work not only reveals new mechanisms for OER but also opens the door for the application of emerging 2D ferromagnets in the field of energy storage and conversion. Abstract : 2D ferromagnetic Fe3 GeTe3 has the potential to be an excellent oxygen evolution reaction (OER) electrocatalyst, as demonstrated in this article. The self‐reduction of surface hydroxyl into water plays a crucial role in lowering the overpotential. This work not only reveals new mechanisms for OER, but also opens the door for utilizing 2D ferromagnets in the field of energy storage and conversion.